STRATEGI MENINGKATKAN PEREKONOMIAN DESA MELALUI OPTIMALISASI PERAN BUMDES DI DESA NGAMPUNGAN KABUPETAN JOMBANG - Septianingrum, Ika Putri Kumalasari; Fanida, Eva Hany (Universitas Negeri Surabaya, 2024)
Village-Owned Enterprises (BUMDes) are one of the institutions that encourage that drives village economic growth towards Independent Villages. BUMDes Maju Sejahtera is one of the 25% advanced BUMDes in Jombang Regency and has experienced rapid growth in the last 5 (five) years. Regarding its strategic management process, it still experiences obstacles such as the development of business units that are not maximized, limited capital, lack of facilities and infrastructure, and lack of community involvement. Even so, BUMDes Maju Sejahtera remains successful and is able to make a number of proud achievements at the district to national level. This research aims to analyze the strategic management used by BUMDes Maju Sejahtera in Ngampungan Village. This research is descriptive research with qualitative approach. The focus of this research is the theory of the strategic management process theory by Ahmad (2020) which consists of strategy formulation, strategy implementation, and strategy evaluation. Data collection techniques used observation, interviews, and documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation, and verification and conclusion making. The results of this study explain that the management strategies used to manage and develop BUMDes Maju Sejahtera are maintaining communication and cohesiveness between management, establishing cooperation with external parties, actively participating in coaching from DPMD, conducting regular deliberations, conducting comparative studies, actively participating in competitions, providing capital injections for units that experience growth delays, and socializing to the community. However, in implementing there are still obstacles related to the limited number of human resources, limited competence and time of the management, and budget funds. The suggestions that can be given include: 1) BUMDes administrators can increase commitment and awareness regarding obligations in BUMDes management, 2) invite cooperation with the Jombang Cooperative and MSME Office, 3) plan and budget for the addition of supporting facilities for business unit development, 4) cooperate with SMK in Bareng Sub-district regarding the acceptance of internship students, 5) submit funding proposals to the district and provincial governments, 6) conduct socialization to the community.